The Impact of the SAVI Approach Assisted by Macromedia Flash on Geometry Learning Outcomes of Students with Different Motivation Levels - Kusuma, Arie Purwa; Triyono, Ageng; Rahmawati, Nurina Kurniasari; Wibowo, Teguh; Ramadoni, Ramadoni (Jurnal Pendidikan Matematika Universitas Lampung, 2026)
The rapid development of science and technology necessitates fundamental transformations in education, particularly through learning innovations that accommodate diverse learning styles, enhance active student engagement, and stimulate intrinsic motivation in mathematics learning. This study aims to examine the effectiveness of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model assisted by Macromedia Flash in improving geometry learning outcomes among eighth-grade students. The research employed a quasi-experimental pretest-posttest design with a control group. A total of 55 students were selected through cluster random sampling and divided into an experimental group (SAVI + Macromedia Flash) and a control group (conventional learning). Learning motivation was measured using a validated questionnaire and categorized into high, medium, and low levels. Macromedia Flash was chosen as a digital medium for its ability to visualize abstract geometric concepts interactively and attractively, thereby facilitating students' understanding of complex material. Data were analyzed using two-way ANOVA to assess the effects of the learning model, motivation level, and their interaction on geometry learning outcomes. The results showed that the SAVI model assisted by Macromedia Flash was significantly more effective in improving geometry learning outcomes than conventional methods (p < 0.05). However, no significant effects were found for motivation level or its interaction with the learning model on learning outcomes. These findings confirm that SAVI-based learning innovations integrated with digital multimedia can optimize geometry learning outcomes evenly, regardless of students' initial motivation levels. This study highlights the practical value of interactive, technology-based approaches in advancing mathematics education.